Regulating energy innovation: US responses to hydraulic fracturing, wastewater injection and induced seismicity. Issue 2 (3rd April 2017) - Stewart, Fenner L; Ingelson, Allan
Abstract : This article focuses on how hydraulic fracturing activities – including wastewater injection – generated, and are still generating, a spectrum of regulatory responses. These regulatory inconsistencies are due to many variables, including: differing opinions on how regulators ought to manage new technologies with unknown environmental impacts; the promise of economic benefit; how politically contested hydraulic fracturing is in the jurisdictions in question; and the fact that much is still unknown about the environmental impacts of hydraulic fracturing. Part I provides an overview of the emerging science on the connections between hydraulic fracturing, wastewater injection and induced seismicity. Part II maps the responses of state-level regulators in the United States to this issue. Part III provides a refresher of the environmental governance theories and practices that help administrative agencies cope with the risks, which energy systems have created, and which agencies are mandated to manage. Part IV evaluates the US state-level responses using the introduced theories and practices. Finally, the conclusion provides some additional reflections.